Root penetration is associated with root diameter and root growth rate in tropical forage grasses - Huot, Chanthy; Philp, Joshua N. M.; Zhou, Yi; Denton, Matthew D. (MDPI, 2025)
Soil compaction impedes root exploration by plants, which limits access to nutrients and water, ultimately compromising survival. The capability of roots to penetrate hard soils is therefore advantageous. While root penetration has been studied in various annual crops, the relationships between root growth and root penetration are poorly understood in tropical perennial grasses. This study aimed to compare root penetration capability in 10 tropical perennial forage grasses and identify relationships between root penetration, root diameter and vertical root growth. Root penetration of each species, namely Urochloa (syn. Brachiaria) brizantha cv. Mekong Briz, U. decumbens cv. Basilisk, U. humidicola cv. Tully, U. hybrid cv. Mulato II, U. mosambicensis cv. Nixon, U. ruziziensis cv Kennedy, Panicum coloratum cv. Makarikariense, Megathyrsus maximus (syn. Panicum maximum) cv. Tanzânia, Paspalum scrobiculatum (syn. Paspalum coloratum) cv. BA96 10 and Setaria sphacelata cv Solendar, was evaluated using wax layers of varying resistances, created from a mixture of 40% (1.39 MPa) and 60% (2.12 MPa) paraffin wax, combined with petroleum jelly. Reference root sizes were determined for the grass species by measuring root diameter and root lengths of seedlings grown in growth pouches. Vertical root growth rate for each species was measured in grasses grown in 120 cm deep rhizotrons. Species with greater root penetration at both resistances had significantly higher shoot growth rates (r = 0.65 at 40% wax and 0.66 at 60% wax) and greater root diameters (r = 0.67 at 40% wax and 0.68 at 60% wax). Root penetration was significantly higher in species with greater vertical root growth rate only in the 60% wax treatment (r = 0.82). Root penetration at higher resistance was correlated with the root diameter and rapid vertical root growth of the species. This may indicate a contribution of these traits to root penetration ability. The combination of greater root diameter and root vertical growth rate, as observed in M. maximus, may assist in the identification of perennial forage grasses suitable for agroecosystems challenged by soil compaction and rapidly drying soil surface.